Single-ion values for ionic solids of both formation enthalpies, ΔfH(298)ion, and Gibbs Formation Energies, ΔfG(298)ion - Glasser, Leslie (American Chemical Society, 2013)
Formation enthalpies, ΔfH(298), are essential thermodynamic descriptors of the stability of materials, with many available from the numerous thermodynamic databases. However, there is a need for predictive methods to supplement these databases with missing values for known and even hypothetical materials, and also as an independent check on the not-always reliable published values. In this paper, we present 34 additive single-ion values, ΔfH(298)ion, from the formation enthalpies of 124 ionic solids, including an extensive group of silicates. In addition, we have also developed an additive set of 29 single-ion formation Gibbs energies, ΔfG(298)ion, for a smaller group of 42 materials from within the full set, constrained by the limited availability of the corresponding experimental data. Such single-ion values may be extended among related materials using simple differences from known thermodynamic values, but always with critical consideration of the results.Using the excellent available data for silicates, we propose that the solid-state silicate ion formation enthalpies can be estimated as −ΔfH(298)silicate/kJ mol–1= −252[n(Si) + n(O)] – 27, where n(X) represents the number of species X in the silicate. More speculatively, we estimate the contribution per silicon and oxygen species as −490 and −184 kJ mol–1, respectively. Similarly, −ΔfG(298)silicate/kJ mol–1= −266[n(Si) + n(O)] – 7, with the contribution per silicon and oxygen species being −140 and −300 kJ mol–1, respectively. We compare and contrast these results with the extensive collection of “modified lattice energy” (MLE) ion parameters from the M.S. thesis of C. D. Ratkey. Our single-ion formation enthalpies and the MLE parameters may be used in complementary predictions. While lattice energies, UPOT, entropies, So298, and heat capacities, Cp,298, of ionic solids are reliably estimated as proportional to their formula volumes (using our Volume-Based Thermodynamic, VBT, procedures), this is not the case in general for thermodynamic formation properties, other than within select groups of related materials.